Necrotizing fasciitis arising from squamous cell carcinoma of the vulva: Case report - Dua Cebeci; Şirin Yaşar; Tevfik Eker; Görgün Bayraktaroğlu (PAGEPress Publications, 2022)
Necrotizing fasciitis (NF) is a devastating soft tissue infection affecting fascias and subcutaneous soft tissues. While it is associated with several risk factors, including malignancy, alcoholism, liver disease, drug use, malnutrition, diabetes, male gender and old age, few case reports in the literature describe its rare connection with genital malignancy. Vulvar squamous cell carcinoma (SCC) is the fourth most common malignancy, representing 5% of all gynaecological tumours among women. NF due to vulvar SCC is a rare complication. In this article, we present the 1991 case of a 58-year-old diabetic female patient with NF due to vulvar SCC. While surgical intervention was successful, the prognosis for vulvar SCC was poor because of late detection.